EGS P28 Transhiatal oesophagectomy to salvage transacted oesophagus from laparoscopic paraoesophageal hernia repair. (7th December 2022) - (Linda) Lin, Yi-Tzu; Almonib, Ahmed; Tan, Benjamin
Abstract: Background: Perforation of oesophagus and stomach during paraoesophageal hernia (POH) repair can be caused by traction on the lower oesophagus, gastro-oesophageal junction (GOJ) and fundus, or a thermal injury from the energy device during dissection. Iatrogenic complete transaction of oesophagus during elective laparoscopic POH repair is extremely rare. Here we reported this unusual complication. Methods: A 79-year-old man with a history of hypertension and hypothyroidism underwent elective laparoscopic POH repair in a district hospital. During the surgery, oesophagus was transacted above the level of GOJ due to constant traction on the lower oesophagus and GOJ. Patient remained haemodynamically stable and was transferred to our tertiary centre next day. Patient was taken to theatre for midline laparotomy. Intraoperatively, stomach, omentum and transverse colon were in the chest and reduced carefully. The oesophageal stump, approximately 20cm from hiatus, was found in the mediastinum with the use of a nasogastric tube. It was also noted that there were several serosal tears on the proximal stomach and left gastric vessels were already divided. Unfortunately, oesophageal stump was ischaemic and friable. Therefore we decided to perform transhiatal oesophagectomy. Oesophagus was fully mobilised via cervical and abdominal incisions and was resected above the level of clavicle. Cervical oesophagogastric anastomosis was performed with semi-mechanical end-to-side EndoGIA 30mm blue and interrupted 3-0 PDS. Postoperatively, he was transferred to intensive care unit for ongoing care. Results: Patient was off inotropes of Day 2 and extubated on Day 3 postoperatively. He developed pneumonia and atrial fibrillation and was treated with intravenous antibiotics and amiodarone. He has recovered well and is currently awaiting transfer to the ward. Conclusions: Complete transection of oesophagus due to of traction in laparoscopic POH is an extremely uncommon complication. Transhiatal oesophagectomy can be considered as a management option in selected cases.